ECTOPIC CUTANEOUS SCHISTOSOMIASIS: REPORT OF TWO CASES AND A REVIEW OF THE LITERATURE - José de Souza ANDRADE FILHO; Maria Sueli S. N. LOPES; Antônio A. CORGOZINHO FILHO; Gil P. M. PENA (Revista do Instituto de Medicina Tropical de São Paulo, 1998)
Two cases of ectopic cutaneous schistosomiasis are described. Both patients presented with abdominal papular skin lesions, which on biopsy were found to contain granulomas with Schistosoma mansoni eggs. Twenty-five other cases were retrieved from the literature. Most patients were female, mean age 24.9 year, with a predominance of the white race. The most common localization was anterior thorax and abdomen. Usually, the lesions were asymptomatic. In few cases, however, severe clinical syndromes due to the parasite coexisted, such as transverse myelitis or the acute-toxemic form of the disease. Intestinal infection was not frequently demonstrated in these patients. The importance of the recognition of these cutaneous lesions may rest on the opportunity to provide an etiological diagnosis in these difficult cases. Dois casos de esquistossomose cutânea ectópica são relatados. Ambos os pacientes apresentavam lesões papulares no abdômen que, ao exame histopatológico, mostraram presença de granulomas contendo ovos de Schistosoma mansoni. Vinte e cinco casos de esquistossomose cutânea ectópica foram encontrados descritos na literatura. A maioria dos pacientes era do sexo feminino, com idade média de 24,9 anos e predominância da raça branca. A localização mais comum foi o tórax anterior e abdômen. Freqüentemente, as lesões eram assintomáticas. Em alguns casos, no entanto, coexistiam alterações sistêmicas graves, relacionadas ao parasito, como mielite transversa e a forma aguda toxêmica da doença. Na maior parte dos casos, a infecção intestinal não pôde ser demonstrada. O reconhecimento destas lesões cutâneas pode ser importante por proporcionar oportunidade para um diagnostico etiológico nestes casos.